Pengaruh Transparansi, Akuntabilitas Dan Partisipasi Masyarakat Dalam Pengelolaan Dana Desa Di Kabupaten Biak Numfor Distrik Biak Timur Kampung Soryar - Lussy, Michi; Bayu Utomo, Rochmad (Cattleya Darmaya Fortuna, 2024)
This study aims to determine the effect of transparency, accountability, and community participation on the management of village funds in Soryar Village, East Biak District, Biak Numfor. This type of qualitative research uses primary data by distributing questionnaires to respondents. The population in this study were all people who lived in Soryar Village, East Biak District, Biak Numfor Regency. The method used is purposive sampling so as to get 60 respondents but use 30 people outside the same district and sub-district. Based on the results of the t test that has been carried out to find out, that transparency and accountability have no significant effect on the management of village funds. Meanwhile, community participation is proven to have a significant effect on the management of village funds.